PERKEMBANGAN SASTRA INDONESIA DI ERA MODERN - Aulia Rachma (Journal of Linguistics, Literature, Culture and History, 2025)
The dynamics of change in modern Indonesian literature in line with modernization, globalization, and advances in digital technology, from the Balai Pustaka era to 2026, during which literature evolved from didactic to digitally expressive forms as a socio-political mirror. The main objective is to analyze the history of development, characteristics, external influences, and challenges and prospects to understand the transformation of themes, styles, and distribution of works. Descriptive qualitative methods through literature study, hermeneutic content analysis, and diachronic periodization utilize primary data (representative literary texts) and secondary data (2025 journals such as Putri, Nugraha, and Riri Satria). The results show a chronological evolution with layered themes (identity, feminism), a hybrid style, digital democratization via Wattpad-TikTok despite the risk of commercialization and low reading interest (0.001 books/capita), with the prospect of Gen Z regeneration through hybrid festivals and digital literacy